Food Consumption as a Risk Factor of Anemia among Indonesian Pregnant Women: A Cross-sectional Study among Javanese Ethnic Group - Anggraeni, Mekar Dwi; Fatoni, Amin; Setiyani, Rahmi (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Anemia during pregnancy causes several adverse effects. Furthermore, in Indonesia, this leads to restrictions among pregnant women. The information on this situation is still limited, and more research needs to be conducted. AIM: Therefore, this study aims to investigate the association between food consumption and anemia among pregnant women. METHODS: This is a cross-sectional descriptive research that involved 424 pregnant women. Furthermore, written informed consent was obtained from respondents before data collection. A self-administered questionnaire was used to assess the food consumption and demographic data. Hemoglobin concentration was further measured using a haemoglobinometer, and data were analyzed using a descriptive statistical Chi-square, and a Multiple Logistic Regression test. RESULTS: It was found that half of the respondents suffered from anemia (46.5%). Furthermore, the Multiple Logistic Regression test showed that tea, liver, eggs, and iron consumption with values of (odds ratio [OR] = 5.075, p < 0.001), (OR = 4.128, p < 0.001), (OR = 3.590, p < 0.01), and (OR = 3.837, p < 0.05), respectively, had significant correlations with anemia among pregnant women. CONCLUSIONS: Anemia is commonly experienced by Indonesian pregnant women. Therefore, health-care providers should focus on preventing anemia in pregnant women by reducing their tea intake and increasing the consumption of iron-rich foods or supplements.